2023
DOI: 10.3390/rs15030662
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Changes, Surface Deformation and Movement Process before, during and after a Rotational Landslide

Abstract: The deformation characteristics and instability patterns of rotational landslides are complicated. Such landslides are large and occur continuously, seriously threatening people’s lives. We used interferometry synthetic aperture radar (InSAR), digital elevation models of difference (DODs), numerical simulations, and other techniques for analyzing the topographic changes, surface deformation and movement process before, during and after a landslide. Based on the high-resolution terrain data before and after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 66 publications
0
38
0
Order By: Relevance
“…We also found that higher water content not only played a positive role in the occurrence of RTSs but also in their activity (Figures 6g, 6h and 7g, 7h). In most places, a wetter environment promotes the occurrence of landslide (Ma et al., 2023; Yang et al., 2021c; Zhang et al., 2022a). The decrease in the soil shear strength during precipitation is the main mechanism of landslide failure (Cogan et al., 2018; Liu et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also found that higher water content not only played a positive role in the occurrence of RTSs but also in their activity (Figures 6g, 6h and 7g, 7h). In most places, a wetter environment promotes the occurrence of landslide (Ma et al., 2023; Yang et al., 2021c; Zhang et al., 2022a). The decrease in the soil shear strength during precipitation is the main mechanism of landslide failure (Cogan et al., 2018; Liu et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, this geomorphological unit is extremely vulnerable to climate change due to elevation‐dependent warming and its delicate natural environment (Kuang & Jiao, 2016; Pei et al., 2023b; Pepin et al., 2015). There is abundant evidence proving that the warming rate on the QTP has been almost twice the global rate during the last four decades (Cheng et al., 2019; CMA Climate Change Centre, 2022; Kang et al., 2010), which is responsible for permafrost degradation and its associated hazards (Ma et al., 2023; Mu et al., 2020; Niu et al., 2012; Qiu et al., 2022; Sun et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical simulation techniques were employed to determine the changes in pore water pressure within the slope by analyzing the infiltration line. The analysis utilized the seepage equation implemented in the SEEP/W module 24 .…”
Section: Macroscopic Deformation Characteristics Of Landslidementioning
confidence: 99%
“…Recently, with the development of science and technology and the theory of multidisciplinary interaction, they provide new opportunities for the research on early detection, dynamic monitoring and risk reduction of unstable slopes (Liu et al, 2022;Wang et al, 2022). However, efficient detection, low-cost monitoring, accurate early warning, and reliable risk assessment still require further breakthroughs (Qu et al, 2021;Ma et al, 2023). Volume I of this Research Topic received 14 manuscripts last year (Nie et al, 2023).…”
Section: Introductionmentioning
confidence: 99%